Hispanic Women and Education Annotated Selected References and Resources. Bibliography Series: 5 - Wheat, Valerie, Comp.; Women's Educational Equity Communications Network, San Francisco, CA. ([Washington, D.C.]] : Distributed by ERIC Clearinghouse, 1978)
The annotated bibliography cites 82 selected references and resources pertaining to Hispanic women. Published between 1969 and 1978, the materials cited include bibliographies, overviews and statistical profiles, curricula and teaching materials, evaluations of material, perspectives on education, and publications on the participation of Hispanic women in the labor force and social, psychological and cultural conflicts (sexual and cultural roles and stereotypes, the immigration experience, and identity and political relationships). Addresses, phone numbers, contact persons, and a brief overview of the organization's interest areas are given for 13 Hispanic organizations and resource groups. Selected for their accessibility and relevance to women's educational equity, the entries were identified by searching ERIC (Educational Resources Information Center), Psychological Abstracts, Sociological Abstracts, National Technical Information Service, Comprehensive Dissertation Abstracts, Magazine Index, Women Studies Abstracts, catalogs and holdings of Chicano and women studies libraries, and Hispanic organizations and projects. Although the U.S. Equal Employment Opportunity Commission's definition of "Hispanic" (all persons of Mexican, Puerto Rican, Cuban, Central or South American, or other Spanish culture or origin) was used, most of the materials are related to Mexican American women. (NQ)
Sponsoring Agency: Office of Education (DHEW), Washington, DC. Women's Program Staff.
ERIC Note: Compiled in consultation with Martha P. Cotera.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Annotated Bibliographies; Cubans; Culture Conflict; Education; Females; Identification (Psychology); Instructional Materials; Labor Force; Mexican American Education; Mexican Americans; Organizations (Groups); Political Affiliation; Puerto Ricans; Reference Materials; Sex Role; Sex Stereotypes; Spanish Speaking; Chicanas; Reference Materials, Bibliographies